2019
DOI: 10.3390/ani9100829
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lameness on the Lying Behaviour of Zero-Grazed Lactating Jersey Dairy Cattle Housed in Straw Yards

Abstract: Simple SummaryLameness is a concern within the dairy industry. Firstly, it has a negative effect on the animal’s welfare, and secondly, has been found to be costly to producers. Ultimately, it can result in having to cull the cow early. Lameness can change the behaviour of cows who may spend more time lying down to relieve the pain in their feet. In this study, we used activity monitors to automatically record the behaviour of non-lame and lame Jersey cattle. Unlike previous studies involving other breeds, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
3
7
0
Order By: Relevance
“…Among cows with easy and unassisted calving, a marked increase in lying bouts is seen starting 6 h before calving, and during the final 24 h before calving, the time spent lying down is reduced by approximately 1 h (Jensen, 2011;Miedema et al, 2011). This may be due to discomfort during contractions, which also increases markedly dur- Hassall et al, 1993;Singh et al, 1993;Cook et al, 2004;Walker et al, 2008;Chapinal et al, 2010a,b;Ito et al, 2010;Blackie et al, 2011;Calderon and Cook, 2011;Thomsen et al, 2012;Yunta et al, 2012;Navarro et al, 2013;Sepúlveda-Varas et al, 2014;Charlton et al, 2016;Solano et al, 2016;Westin et al, 2016;Weigele et al, 2018;Blackie and Maclaurin, 2019;Thompson et al, 2019) or mastitic cows relative to controls (n = 7 papers; Siivonen et al, 2011b;Zimov et al, 2011;Cyples et al, 2012;Fogsgaard et al, 2012;Medrano-Galarza et al, 2012;Yeiser et al, 2012;Fogsgaard et al, 2015). The dashed vertical line indicates 100%, or that the control and affected animals had the same values.…”
Section: Reproductive State and Stage Of Lactationmentioning
confidence: 99%
“…Among cows with easy and unassisted calving, a marked increase in lying bouts is seen starting 6 h before calving, and during the final 24 h before calving, the time spent lying down is reduced by approximately 1 h (Jensen, 2011;Miedema et al, 2011). This may be due to discomfort during contractions, which also increases markedly dur- Hassall et al, 1993;Singh et al, 1993;Cook et al, 2004;Walker et al, 2008;Chapinal et al, 2010a,b;Ito et al, 2010;Blackie et al, 2011;Calderon and Cook, 2011;Thomsen et al, 2012;Yunta et al, 2012;Navarro et al, 2013;Sepúlveda-Varas et al, 2014;Charlton et al, 2016;Solano et al, 2016;Westin et al, 2016;Weigele et al, 2018;Blackie and Maclaurin, 2019;Thompson et al, 2019) or mastitic cows relative to controls (n = 7 papers; Siivonen et al, 2011b;Zimov et al, 2011;Cyples et al, 2012;Fogsgaard et al, 2012;Medrano-Galarza et al, 2012;Yeiser et al, 2012;Fogsgaard et al, 2015). The dashed vertical line indicates 100%, or that the control and affected animals had the same values.…”
Section: Reproductive State and Stage Of Lactationmentioning
confidence: 99%
“…Main daily activities of ruminants include eating, ruminating, and resting; therefore, these behaviors were the target of our behavioral observation using the sensor data. These behaviors are particularly important because changes in their duration or frequency can be a potential way to monitor welfare and health status of ruminants ( Weary et al, 2009 ; Medrano-Galarza et al, 2012 ; Blackie and Maclaurin, 2019 ). The least-square means for sensor data for the recorded behaviors are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Blackie et al [21] reported differences in lying time between zero-grazing lame and nonlame Holsteins. Subsequently, Blackie and Maclaurin [22] in a similar study did not find similar associations with Jersey cows. Behavior-lameness associations could thus fail to generalize depending on the severity of lameness, grazing/zero-grazing, and breed.…”
Section: Introductionmentioning
confidence: 84%
“…The severity of lameness and how easily it can be detected using behavior are likely to be associated. Some studies [18,22,37] have investigated a greater range of lameness severity than the present study. The present findings indicate that mild and moderate lameness is difficult to detect, whereas severe lameness detection might be more easily achieved.…”
Section: Study Limitationsmentioning
confidence: 90%